2012
DOI: 10.1002/ppul.22526
|View full text |Cite
|
Sign up to set email alerts
|

Baseline and post‐bronchodilator interrupter resistance and spirometry in asthmatic children

Abstract: In children unable to perform reliable spirometry, the interrupter resistance (R(int) ) technique for assessing respiratory resistance is easy to perform. However, few data are available on the possibility to use R(int) as a surrogate for spirometry. We aimed at comparing R(int) and spirometry at baseline and after bronchodilator administration in a large population of asthmatic children. We collected retrospectively R(int) and spirometry results measured in 695 children [median age 7.8 (range 4.8-13.9) years]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
1
20
0
2
Order By: Relevance
“…The lack of importance of sRtot in other studies might be explained by its too high variability in schoolchildren or weak relation between baseline FEV 1 and sRtot, which has been reported. 14, 15 Beydon et al 12 found that the baseline relation between FEV 1 and sRtot was weak in large group of schoolchildren. The same could be true for other spirometric indices in the present study, based on previous results.…”
Section: Discussionmentioning
confidence: 98%
“…The lack of importance of sRtot in other studies might be explained by its too high variability in schoolchildren or weak relation between baseline FEV 1 and sRtot, which has been reported. 14, 15 Beydon et al 12 found that the baseline relation between FEV 1 and sRtot was weak in large group of schoolchildren. The same could be true for other spirometric indices in the present study, based on previous results.…”
Section: Discussionmentioning
confidence: 98%
“…(7) The interrupter technique has good repeatability (21) and, like FOT, can detect changes in airway caliber acutely and in response to bronchodilators. (22) Again, severe bronchial obstruction and variations in upper airway compliance may result in underestimation of alveolar pressure; however, the interrupter technique has been studied in asthma, (23) CF, (24) and bronchiolitis. (25) …”
Section: Forced Oscillation Techniquementioning
confidence: 99%
“…Prospective cohort studies that assessed the association of maternal hemoglobin or hematocrit levels with childhood lung function and asthma are scarce, 16,17 and show inconsistent results. We aimed to address all factors that explained differences in results of the previous studies into account, and now used both hemoglobin and hematocrit levels, WHO clinical cut-off definitions, lung function measured by spirometry, which is an objective and reliable 29,30 method, took gestational age at blood sampling and multiple confounders into account, and explored intermediating and effect modifying factors. We observed associations of maternal hemoglobin and hematocrit levels measured in early pregnancy with lower childhood lung function, but not with asthma at age 10 years.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…We used a population-based prospective cohort design from early pregnancy onwards, with detailed information on maternal and child characteristics and on maternal red blood status. Spirometry is the preferred method to assess lung function, 29,30,38 and to date this is the first study that uses this method as asthma-related outcome with maternal hemoglobin and hematocrit levels during pregnancy and long-term pulmonary outcomes under study. However, some limitations do apply.…”
Section: Strengths and Limitationsmentioning
confidence: 99%